Conflict during the day keeps you unbalanced at night: a daily investigation of work task conflict, coworker support and work-family balance. Issue 3 (23rd February 2022) - Wan, Min (Maggie); Zhang, Yejun; Shaffer, Margaret A.; Li, Mingze; Zhang, Guanglei
Abstract : Purpose: Drawing on job demands-resources theory (Bakker and Demerouti, 2017) and conservation of resources theory (Hobfoll, 1989), this study aims to investigate the roles of work task conflict and coworker support in the experience of daily work-family balance. In particular, this study theorizes work-family balance as a higher-order construct, including both psychological (work-family balance satisfaction) and social (work-family balance effectiveness) dimensions. Design/methodology/approach: The authors tested the proposed model using daily diary survey data collected from 50 full-time corporate employees across five consecutive workdays in a week. The hypotheses were tested using multilevel modeling analyses. Findings: Analyses show that work task conflict impedes employees' work-family balance on a daily basis. Results also support the moderating role of coworker support, such that the negative relationship between work task conflict and work-family balance is weaker when coworker support is high. Originality/value: This research contributes to the literature by considering work-family balance as a higher-order construct. Further, this research advances theoretical knowledge of the interpersonal predictors of work-family balance. This study also expands previous work by examining the dynamic relationships between interpersonal events and work-family balance.